Integration of ANP and TOPSIS Methods in Prioritizing Sales Strategies for Frozen Food Products - Kamil, Hamdani; Mukhlis, Mukhlis; Bachtiar, Yahya (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2023)
This research is about determining the best marketing strategy In Frozen Food Products. This Company is a food industry in the form of nuggets, sausages, batagor, empek-empek, meatballs, burgers, and risoles. For the next few years, the Company will be in a growth phase position, which is at the stage of development of increasing sales. Therefore, it is necessary to do mentoring and evaluation to increase sales. Still, the problems that often occur in the Company are: cannot market products in the modern market and hotels and marketing strategies that are less effective in increasing sales results. This certainly has an impact on achieving sales targets. Based on these problems, an assessment and selection of the best strategy is carried out the best design that will be chosen and maintained by the Company in increasing sales at IKM X. Based on the processing of the ANP Method and using Superdecision Software, the weight of product criteria is obtained into selected criteria with a percentage weight of 27.06%. Using the TOPSIS method, the top priority of the new marketing alternative for frozen food products that match the product criteria is the taste according to consumer taste because it has the most significant preference value of 0.8891.